Effects of general and corona-specific stressors on mental burden during the SARS-CoV-2 pandemic in Germany - Hubenschmid, Lara; Helmreich, Isabella; Köber, Göran; Gilan, Donya; Frenzel, Svenja B.; Dick, Rolf van; Lieb, Klaus (Frontiers in Public Health, 2022)
The SARS-CoV-2 pandemic turned out to be a serious threat to mental and physical health. However, the relative contribution of corona-specific (DHs) and general stressors (DHg) on mental burden, and specific protective and risk factors for mental health are still not well understood. In a representative sample (N = 3,055) of the German adult population, mental health, potential risk, and protective factors as well as DHs and DHg exposure were assessed online during the SARS-CoV-2 pandemic (June and July 2020). The impact of these factors on mental health was analysed using descriptive statistics, data visualizations, multiple regressions, and moderation analyses. The most burdensome DHg were financial and sleeping problems, respectively, and DHs corona-media reports and exclusion from recreational activities/important social events. 31% and 24% of total mental health was explained by DHg and DHs, respectively. Both predictors combined explained 36%, resulting in an increase in variance due to DHs of only 5% (R2 adjusted). Being female, older and a lower educational level were identified as general risk factors, somatic diseases as a corona-specific risk factor, and self-efficacy and locus of control (LOC) proved to be corona-specific protective factors. Further analyses showed that older age and being diagnosed with a somatic illness attenuated the positive influence of LOC, self-efficacy, and social support on resilience. Although the data showed that after the first easing restrictions, the stressor load was comparable to pre-pandemic data (with DHs not making a significant contribution), different risk and protective factors could be identified for general and corona-specific stressors. In line with observations from network analysis from other groups, the positive impact of resilience factors was especially diminished in the most vulnerable groups (elderly and somatically ill). This highlights the need to especially target these vulnerable groups to foster their resilience in upcoming waves of the corona pandemic.